Stress Influences the Effect of Obsessive-Compulsive Symptoms on Emotion Regulation - Ferreira, Sónia; Couto, Beatriz; Sousa, Mafalda; Vieira, Rita; Sousa, Nuno; Picó-Pérez, Maria; Morgado, Pedro (Frontiers in Psychiatry, 2021)
Obsessive-compulsive disorder (OCD) is associated with emotion regulation impairments, namely the frequent use of maladaptive strategies such as suppression and the decreased use of reappraisal strategies. Additionally, these patients exhibit elevated stress levels. Since stress exposure affects emotion regulation abilities, stress might influence the relationship between obsessive-compulsive symptoms and emotion regulation. In this study, we explored the effects of stress and obsessive-compulsive symptoms on emotion regulation in a sample of healthy and OCD individuals. We used self-reported psychometric scales to measure stress levels, obsessive-compulsive symptoms, and emotion reappraisal and suppression skills. We applied multiple regression and mediation analyses. Our results demonstrated that increased reappraisal scores were associated with higher suppression scores. Additionally, elevated stress values predicted increased scores for suppression and decreased scores for reappraisal. Furthermore, the reappraisal abilities resulted from a combination of a direct effect of obsessive-compulsive symptoms and an indirect effect of obsessive-compulsive symptoms mediated by stress. The reliance on suppression strategies and the difficulty in using reappraisal approaches are explained by stress levels and are not directly explained by obsessive-compulsive symptoms. This study highlights the necessity of targeting stress in current therapy-based treatments for OCD.